Effects of Epidural Test Dose Volume on Skin Perfusion, Temperature, and Reflex Vasoconstriction. Issue 1 (January 1994) - Valley, Marc A.; McKenzie, Anne M.; Bourke, Denis L.; Raja, Srinivasa N.
Abstract : Background and Objectives: The authors sought to define the effects of differing volumes of epidural test dose on skin perfusion, skin temperature, and reflex vasoconstriction to a maximal inspiration (inspiratory gasp vasoconstrictive response, IGVR). Methods: With informed consent and Institutional Review Board approval, the authors studied 40 patients undergoing epidural anesthesia. Skin perfusion was monitored in glabrous skin on the foot using laser Doppler. Inspiratory gasp vasoconstrictive response and temperature measurements were obtained at 1-minute intervals. After a baseline period, 5 patients received 60 mg intravenous lidocaine HCl; 5 received 5 mL normal saline, via epidural catheter; and 30 patients received 50 mg lidocaine HCl and 20 mcg epinephrine in 2.5, 5.0, or 7.5 mL normal saline (10 patients each). Inspiratory gasp vasoconstrictive response was defined as the percent change in perfusion from baseline produced by an inspiratory gasp. Perfusion was normalized by expressing each patient's value as a percentage of the respective baseline value. Results: Significant increases in perfusion, of up to 169% of baseline, were seen 12 minutes after the test dose. Inspiratory gasp vasoconstrictive response showed significant changes from baseline in all test groups. The temperature change was insignificant. Control groups did not show perfusion or IGVR changes. Conclusions: Skin perfusion and IGVR changed significantly after epidural test dose; the minimal effect of volume appears to be 5 mL of lidocaine-epinephrine solution; the presence of IGVR or perfusion changes, or both, are positive predictors of successful placement of the catheter into the epidural space; and temperature changes as observed here were not reliable predictors of proper placement of epidural catheters.